ミクログリアによるニューロンーアストロサイト間情報伝達の制御機構 - 鈴木, 秀明; 高橋, 由香里; 加藤, 総夫; 尾藤, 晴彦; 小泉, 修一; 繁冨, 英治; 池中, 一裕; 平山, 幸歩; 田中, 謙二 (日本薬理学会年会要旨集, 2022)
Astrocytes become reactive upon injury and inflammation in the brain to alter their molecular profiles, morphologies and functions. Reactive astrocytes alter the expression of receptors which are responsible for their functions especially communications in neuron-glia and glia-glia. Among such receptors, the expression of P2Y1 receptors (P2Y1) is upregulated in many neurological diseases including epilepsy and Alzheimer's disease, in which neuronal hyperexcitability is commonly observed. We have previously shown that P2Y1 upregulation in astrocytes trigger neuronal hyperexcitability by enhancing neuron-astrocyte communications. However, the mechanism underlying the upregulation of P2Y1 in astrocytes remains unknown. We investigated the role of microglia in enhanced P2Y1R signaling in astrocytes during pathological conditions. To ask whether microglia play a role in P2Y1 upregulation in astrocytes, we depleted microglia by treatment with PLX5622 and found much larger Ca2+ elevation evoked by a P2Y1 agonist and more P2ry1 transcripts in astrocytes. Microglia depletion enhanced extracellular ATP level presumably through impairment of degradation of ATP. These findings suggest that microglia should has an important role to control P2Y1 receptor expression in astrocytes and negatively regulate neuron-astrocyte communication.